Respons Pertumbuhan dan Rendemen Minyak Klon Nilam (Pogostemon cablin Benth) terhadap Aplikasi Berbagai Dosis Urea (Growth Response And Yield Of Patchouli Clones (Pogostemon Cablin Benth) On Dose Urea Various Applications) - Retno Ayu Diah Pangestu; M. Tahir; Fatahillah Fatahillah (Politeknik Negeri Lampung, 2020)
Patchouli (Pogostemon cablin Benth) is a plant known to produce essential oils, and is also an important foreign exchange earner for Indonesia. However, the use of superior clones and appropriate fertilizers tend to drastically increase product yield. This research aims to obtain species with the best response to urea fertilizers, and the right dosage for optimum performance. The study was conducted at the Politeknik Negeri Lampung’s teaching farm from December 2018 to May 2019, using a factorial randomized block design (RBD). This consisted of two treatment factors, including the 2 level clone consisting of The NPL 9 and Lhokseumawe, and 4 level urea dose control at, 250 kg.ha-1, 300 kg.ha-1, and 350 kg.ha-1. Furthermore, variables observed included plant’s height, bough, diameter, number of leaves, stalk angle, chlorophyll content, wet weight of plant, wind dry weight of plant, and yield. The results shows NPL 9 clone has a superior appearance and the urea value of 350 kg.ha-1 was attributed as the optimal dose, yielding a 2,3% increase compared to the control treatment.